Anguina paludicola sp. n. (Tylenchida: Anguinidae): The nematode associated with Rathayibacter toxicus infection in Polypogon monspeliensis and Lachnagrostis filiformis in Australia - Bertozzi, Terry; Davies, Kerrie A. (Zootaxa, 2009)
Anguina paludicola sp. n. is described from Polypogon monspeliensis from southeastern South Australia and Lachnagrostis filiformis from northern New South Wales, following an examination of nematode populations by allozyme electrophoresis and morphological analysis. Genetic differences were consistent with those expected from conspecific allopatric populations and were based on geography rather than host. Morphological differences between nematodes from P. monspeliensis and L. filiformis were inconsistent and varied between different gall types on the same host plant. The new species is characterised by adults with irregular and variable tail termini, which appear lobed; females may have a process of vestigial ovary extending from the post uterine sac towards the tail; males are dorsally curved with a single reflexed testis; and the haploid chromosome complement is n=18.